2017
DOI: 10.3847/2041-8213/aa6c26
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Tale of Hercules: How Stars Orbiting the Lagrange Points Visit the Sun

Abstract: We propose a novel explanation for the Hercules stream consistent with recent measurements of the extent and pattern speed of the Galactic bar. We have adapted a made-to-measure dynamical model tailored for the Milky Way to investigate the kinematics of the solar neighborhood (SNd). The model matches the 3D density of the red clump giant stars (RCGs) in the bulge and bar as well as stellar kinematics in the inner Galaxy, with a pattern speed of 39 km s −1 kpc −1 . Cross-matching this model with the Gaia DR1 TG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
154
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(173 citation statements)
references
References 46 publications
18
154
1
Order By: Relevance
“…Notice that the orbits associated with the overdensity at (−vR, v φ ) ≈ (−10, 210) km s −1 in the central panel of Fig. 5 are of the same kind of those described by Pérez-Villegas et al (2017), i.e., trapped around the bar's Lagrangian points (see Fig. 6).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Notice that the orbits associated with the overdensity at (−vR, v φ ) ≈ (−10, 210) km s −1 in the central panel of Fig. 5 are of the same kind of those described by Pérez-Villegas et al (2017), i.e., trapped around the bar's Lagrangian points (see Fig. 6).…”
Section: Resultsmentioning
confidence: 74%
“…5) it occurs at −vR > 0, as predicted by the Eulerian linear theory, and as such conflicts with the observations. Hence, the pendulum formalism is mandatory if one seeks to explain the Hercules group as a consequence of the corotation resonance, as Pérez-Villegas et al (2017) did with made-to-measure N -body models. Notice that the orbits associated with the overdensity at (−vR, v φ ) ≈ (−10, 210) km s −1 in the central panel of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…the bar's pattern speed is not greater than ωp = 40 km s −1 , with the consequence that the OLR lies well outside R0 and could only affect local velocity space at positive values of V . With the lower pattern speed we instead lie not far outside the bar's CR, and Pérez-Villegas et al (2017) have shown that the model of the bar developed by Wegg et al (2015) with ωp = 39 km s −1 kpc −1 predicts a feature rather like the Hercules stream that is caused by stars trapped into libration around the Lagrange point L4. Fig.…”
Section: Orbits Trapped At the Olrmentioning
confidence: 80%
“…Sormani et al (2015) concluded that the bar's pattern speed is ωp ≃ 40 km s −1 kpc −1 , a value that coincides nicely the estimate obtained by Wegg et al (2015) by modelling the kinematics of bulge stars. Pérez-Villegas et al (2017) show that ωp = 39 km s −1 correctly predicts the kinematics of solar-neighbourhood stars because it causes stars trapped by corotation to visit the solar neighbourhood in the form of the "Hercules stream". Over the previous two decades larger values ∼ 55 km s −1 kpc −1 were favoured, in part on account of a significant under-estimate of the length of the bar by and in part through the Hercules stream being supposed to arise by trapping at the OLR rather than corotation (Dehnen 1998;).…”
Section: Sormanimentioning
confidence: 84%
See 1 more Smart Citation